Good Governance dalam Membangun Masa Depan Indonesia - Abd. Holik (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
This writing attempts to lift phenomena of the presidential election that occurred in Indonesia, where the real transfer of power (succession) is a necessity that occurs every five years. Seeing this phenomenon brings to the understanding that the selection should be used as a vehicle to remain utilize common sense, so appears virtue is constantly being developed and perpetuated together- at the same time cohabitation conflictual between two things of contradiction that can be dammed as much as possible. In case this is related democracy with oligarchy, democracy coupled with structured crime neatly and such. The issue is raised in an effort to keep perpetuating the concept of good governance in order to achieve good governance. The bid to earthing concept of good governance to build a future in Indonesia showed significance to be retained and developed together here. For that will be revealed in this writing the application from the concept of good governance with the point of view in Islamic law.